Efferent and Afferent Connections of Neuropeptide Y Neurons in the Nucleus Accumbens of Mice - Yamada, Shunji; van Kooten, Nienke; Mori, Takuma; Taguchi, Katsutoshi; Tsujimura, Atsushi; Tanaka, Masaki (Frontiers in Neuroanatomy, 2021)
Neuropeptide Y (NPY) is a neural peptide distributed widely in the brain, and has various functions in each region. We previously reported that NPY neurons in the nucleus accumbens (NAc) are involved in the regulation of anxiety behavior. Anterograde and retrograde tracing studies suggest that neurons in the NAc project to several areas, including the lateral hypothalamus (LH) and ventral pallidum, and receive afferent projections from the cortex, thalamus and amygdala. However, the neural connections between accumbal NPY neurons and other brain areas in mice remain unclear. In the present study, we sought to clarify these anatomical connections of NPY neurons in the NAc by investigating their neural outputs and inputs. To selectively map NPY neuronal efferents from the NAc, we injected Cre-dependent AAVs into the NAc of NPY-Cre mice. This revealed that NAc NPY neurons exclusively project to the LH. We confirmed this by injecting cholera toxin b subunit, a retrograde tracer, into the LH, and found that approximately 7%–10% of NPY neurons in the NAc were double-labeled for mCherry and cholera toxin b subunit. Moreover, retrograde tracing using recombinant rabies virus also identified NAc NPY projections to the LH. Finally, we investigated monosynaptic input to the NPY neurons in the NAc using recombinant rabies virus. We found that NPY neurons in the NAc receive direct synaptic connections from the midline thalamic nuclei and posterior basomedial amygdala. These findings provide new insight into the neural networks of accumbal NPY neurons, and should assist in elucidating their functional roles.